(untitled) (Jurnal Arsitektur ARCADE, 2026)
The building sector is a significant contributor to global carbon emissions, making it necessary to develop strategies to reduce emissions, particularly during the renovation of commercial buildings such as hotels. This study aims to investigate the application of circular economy principles in hotel building renovations to support carbon emission reduction, particularly embodied carbon. The method used is a descriptive qualitative approach through in-depth interviews with four architecture practitioners selected via purposive sampling. Data were analyzed thematically and validated through triangulation with the literature. The results indicate that relevant circular economy strategies include retaining existing structures (intensive use), extending the building’s lifespan, utilizing modular prefabrication, selecting low-carbon materials, and implementing material reuse. The findings also suggest that reuse is more effective than recycling in reducing emissions because it does not require additional energy-intensive processes. Overall, integrating circular economy principles into hotel building renovations has significant potential to reduce carbon emissions and support more sustainable design practices.